الآثار الخارجية للسياحة وطرق معالجتها مع دراسة إمكانية تطبيق نظرية كوز - شريقي طرفة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The goal of this paper is to define both positive and negative externalities of tourism sector. The researcher refers to the most common methods of dealing with external impacts of tourism. The paper studies the basic element of Coase’s Theorem about transactions costs and the possibility of its implementation on tourism sector through a study of establishing a resort with external benefits in Lattakia. The research tries to answer questions about the potential of reducing government intervention in handling external impact of tourism. As well, do the mechanisms proposed by Coase in his theorem allow for the handling of the external impacts of tourism? The papers reaches conclusions on the possibilities of applying the Coase Theorem and the accompanying limitations. The researcher advocates using government intervention tools rather than Coase Theorem mechanisms in the case of tourist activities in Lattakia, especially because of the consequences of the crisis. يهدف هذا البحث إلى تحديد مفهوم الآثار الخارجية للسياحة بجانبيها الإيجابي والسلبي. ويعرض الباحث الطرق الأكثر شيوعاً لمعالجة هذه الآثار. وينتقل البحث إلى دراسة نظرية كوز حول تكاليف الصفقات فيشرح الأفكار الرئيسية المكونة لهذه النظرية، ثم يناقش إمكانية تطبيق آليات هذه النظرية على قطاع السياحة، من خلال دراسة لإقامة منتجع سياحي في مدينة اللاذقية يترافق مع وجود آثار خارجية إيجابية. يحاول البحث الإجابة عن أسئلة حول إمكانية تقليل تدخل الدولة في معالجة الآثار الخارجية للسياحة، وهل تتيح الآليات التي اقترحها كوز في نظريته معالجة الآثار الخارجية للسياحة. ويصل البحث في الختام إلى مجموعة من النتائج حول إمكانيات تطبيق نظرية كوز والقيود المرافقة لذلك، ويبين الباحث أفضلية استخدام أدوات التدخل الحكومي على آليات نظرية كوز في حالة الأنشطة السياحية في اللاذقية وخاصة بسبب تبعات الأزمة.